Remote teaching of physical education during the COVID-19 pandemic in Poland - Korcz, Agata; Krzysztoszek, Jana; Łopatka, Marlena; Bronikowski, Michał (Physical education, sport and olympism from a pedagogical perspective, 2023)
The implementation of physical education remote teaching during the COVID-19 pandemic encountered particular difficulties due to the specificity of the subject. The aim of the study was to get to know the opinions of physical education teachers on distance teaching, which was in the scope of their responsibilities.Among the advantages of remote teaching, the surveyed teachers emphasised the use of modern technologies in practice (67,6%), an easier implementation of the content of the Core Curriculum (CC) related to health education (34,2%), and for 27% of teachers, the remote teaching gave the possibility of greater control and independence of students. Among the shortcomings, the respondents indicated primarily the inability to carry out tasks correctly (72,2%). Moreover, the negative aspects included limited contact with students (61,9%), as well as difficulties in implementing the content of the CC in terms of physical development and physical fitness (57,3%).The surveyed group of the physical education teachers mostly reacted well to the crisis situation, using their creativity, available sources, as well as multimedia possibilities. Undoubtedly, the epidemic situation has shown how comprehensive the preparation of teachers for work in the modern education system should be.